Kajian Literatur tentang Kemampuan Pemimpin Lembaga Pendidikan dalam Menyelesaikan Masalah - Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2025)
This study aims to comprehensively analyze the capacity of educational institution leaders in managing institutional problem-solving processes through a qualitative literature review approach that focuses on integrating theoretical concepts and contemporary educational leadership practices. The study highlights critical stages of leadership, including problem identification and diagnosis, the design of contextually relevant solution strategies, the implementation of adaptive actions, and reflection-based evaluation to ensure continuous improvement. The synthesis of the literature reveals that successful problem-solving is significantly influenced by leaders’ ability to integrate transformational, instructional, and adaptive leadership styles that foster collective participation, professional collaboration, and the establishment of a progressive learning culture. Effective leadership is characterized by reflective capacity, data-driven decision-making, and the ability to create a supportive work climate for innovation and change. Conversely, recurring challenges include limited resources, resistance to transformation, misaligned external policies, and administrative burdens that constrain managerial flexibility. Based on these findings, this study emphasizes the importance of developing context-based leadership models that position problem-solving as a core competency through enhanced data literacy, emotional intelligence, and continuous reflective learning. The main contribution of this article lies in strengthening the theoretical foundation of 21st-century educational leadership and providing practical recommendations for school leaders, policymakers, and leadership training developers to build resilient, adaptive, and continuously improving educational organizations.